1992
DOI: 10.1210/endo.130.4.1547741
|View full text |Cite
|
Sign up to set email alerts
|

Evidence suggesting that insulin-like growth factor-I is necessary for the trophic effects of insulin on cartilage growth in vivo.

Abstract: The possibility that insulin-stimulated cartilage growth in hypophysectomized rats involves local production of insulin-like growth factor I (IGF-I) was investigated. Osmotic minipumps with attached catheters were used to infuse insulin into the right hindlimb of rats via the common iliac artery for 7 days starting 14 days after pituitary removal. The left, noninfused limb served as an internal control. Doses of insulin ranging from 0.25 to 50 mU/day caused significant increases in the tibial epiphyseal plate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…They also postulated that insulin acts directly on chondrocyte maturation without utilizing the secondary pathway of binding to IGF-I receptors. Indeed, in vivo (17) but not in vitro (24), the local production of IGF-I is apparently necessary for the growth-promoting role of insulin. Quarto et al (25) also showed that FGF-2 induces chondrocyte proliferation if associated with insulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also postulated that insulin acts directly on chondrocyte maturation without utilizing the secondary pathway of binding to IGF-I receptors. Indeed, in vivo (17) but not in vitro (24), the local production of IGF-I is apparently necessary for the growth-promoting role of insulin. Quarto et al (25) also showed that FGF-2 induces chondrocyte proliferation if associated with insulin.…”
Section: Discussionmentioning
confidence: 99%
“…At low concentrations, insulin increases parameters of growth, metabolism and muscle differentiation in 4-day-old chick embryos (16). Insulin has been shown to have an in vitro stimulatory effect on chondrocyte proliferation and activity and an in vivo effect on growth plate width (17). Also, situations of hypoinsulinemia (insulin-dependent diabetes mellitus) and hyperinsulinemia with or without non-insulin-dependent diabetes considerably alter normal bone physiology (18).…”
Section: Introductionmentioning
confidence: 99%
“…In the animal experimental study evaluating the effect of insulin on the tibial growth epiphysis, it was found that insulin caused an increase in the growth plate width and this effect was increased by increasing the amount of IGF-1 in the environment. 34 In the same study, it was observed that the effect of insulin reached a maximum in a certain dose range and then decreased its effect. With regard to previous studies, it can be assumed that insulin may have a safe dose range and may damage healing tissue concentration-related when the dose is incorrect.…”
Section: Smentioning
confidence: 90%